Improvement of Voltage Profile in Hybrid PV-Wind System using STATCOM - et. al., Jella Ramakrishna, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With multiple renewable sources connected to the grid, different voltage profile problems are introduced which include voltage sags and fluctuations. These problems are solved by different FACTs devices connected at PCC improving the voltage profile. This paper discusses the STATCOM module integrated into a grid with a FIS structure in the controller for better results as compared to conventional controllers. The distribution grid considered for the analysis comprises of PVA module and PMSG wind farm as renewable energy resources connected at PCC in parallel to the main grid and STATCOM. The analysis is carried out on the proposed distribution test system with different operating conditions using MATLAB software Simulink block sets. All comparison graphs are generated using ‘powergui’ toolbox with time domain analysis.